2023
DOI: 10.1186/s13014-023-02231-6
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT standardized uptake value and EGFR expression predicts treatment failure in nasopharyngeal carcinoma

Abstract: Objective This study inventively combines epidermal growth factor receptor (EGFR) expression of the primary lesion and standardized uptake value (SUV) of positron emission tomography and computed tomography (PET/CT) to predict the prognosis of nasopharyngeal carcinoma (NPC). This study aimed to evaluate the predictive efficacy of maximum standard uptake value (SUVmax) and EGFR for treatment failure in patients with NPC. Methods This retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, we identified that combining TNM stage with other prognostic scores still improved the prognostic performance, which is consistent with the findings reported in previous studies [ 8 , 28 , 35 ]. FDG-PET/CT images, given the capabilities in providing tumors’ metabolic and anatomical information, have also been widely used for prognostic prediction [ 41 43 ]. However, the conventional FDG-PET/CT-derived parameters (SUV, MTV, and TLG) cannot serve as effective prognostic indicators in our univariate analysis (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we identified that combining TNM stage with other prognostic scores still improved the prognostic performance, which is consistent with the findings reported in previous studies [ 8 , 28 , 35 ]. FDG-PET/CT images, given the capabilities in providing tumors’ metabolic and anatomical information, have also been widely used for prognostic prediction [ 41 43 ]. However, the conventional FDG-PET/CT-derived parameters (SUV, MTV, and TLG) cannot serve as effective prognostic indicators in our univariate analysis (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%